Deciphering the Role of Trehalose in Tripartite Symbiosis Among Rhizobia, Arbuscular Mycorrhizal Fungi, and Legumes for Enhancing Abiotic Stress Tolerance in Crop Plants - Sharma, Mahaveer P.; Grover, Minakshi; Chourasiya, Dipanti; Bharti, Abhishek; Agnihotri, Richa; Maheshwari, Hemant S.; Pareek, Ashwani; Buyer, Jeffrey S.; Sharma, Sushil K.; Schütz, Lukas; Mathimaran, Natarajan; Singla-Pareek, Sneh L.; et al. (Frontiers in Microbiology, 2020)
Drought is a critical factor limiting the productivity of legumes worldwide. Legumes can enter into a unique tripartite symbiotic relationship with root nodulating bacteria of genera Rhizobium, Bradyrhizobium, or Sinorhizobium, and colonization by arbuscular mycorrhizal fungi (AMF). Rhizobial symbiosis provides nitrogen (N) necessary for growth. AMF symbiosis enhances uptake of diffusion-limited nutrients such as P, Zn, Cu, etc. and also water from the soil via plant-associated fungal hyphae. Rhizobial and AMF symbioses can act synergistically in promoting plant growth and fitness, resulting in overall yield benefits under drought stress. One of the approaches that rhizobia use to survive under stress is the accumulation of compatible solutes, or osmolytes, such as trehalose. Trehalose is a non-reducing disaccharide and an osmolyte reported to accumulate in a range of organisms. High accumulation of trehalose in bacteroids during nodulation protects cells and proteins from osmotic shock, desiccation, and heat under drought stress. Manipulation of trehalose cell concentrations has been directly correlated with stress response in plants and other organisms, including AMF. However, the role of this compound in the tripartite symbiotic relationship is not fully explored. This review describes the biological importance and role of trehalose in the tripartite symbiosis between plants, rhizobia, and AMF. In particular, we review the physiological functions and molecular investigations of trehalose carried out using omics-based approaches. This review will pave the way for future studies investigating possible metabolic engineering of this biomolecule for enhancing abiotic stress tolerance in plants.